Pharmacognosy - Kokate, C. K.; Purohit, A. P.; Gokhale, S. B. (Pune : Nirali Prakashan, 2009)
Text of modern pharmacognosy covering cultivation technology, quality control of herbal drugs, phytochemistry, phytopharmacy and therapeutic utility of crude drugs. The emphasis is laid on current trends in herbal drugs, nutraceuticals, ayurvedic pharmacy, marine pharmacognosy, medicinal plant biotechnology and endangered species of medicinal plants including plant vaccines, omega-3 fatty acids, hypericin, spirulina, forskolin, jojoba oil, camptothecin, feverfew, echinacea
Includes bibliographical references and index
Keywords: Pharmacognosy; Pharmaceutical biotechnology